2016
DOI: 10.1007/s10533-016-0289-2
|View full text |Cite|
|
Sign up to set email alerts
|

The carbon dioxide evasion cycle of an intermittent first-order stream: contrasting water–air and soil–air exchange

Abstract: The carbon dioxide evasion cycle of an intermittent first-order stream: contrasting water-air and soil-air exchange. Biogeochemistry, 132(1), pp. 87-102. (doi:10.1007/s10533-016-0289-2) This is the author's final accepted version.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/133460/ Ephemeral streams and wetlands are characterized by complex cycles of submersion and 26 emersion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 99 publications
(7 reference statements)
6
24
1
Order By: Relevance
“…The unsubmerged surface of GBs has been shown to have significantly higher CO 2 evasion fluxes, as compared with the equivalent area of its adjacent stream (Boodoo, Trauth, Schmidt, Schelker, & Battin, ). These observed CO 2 evasion flux patterns are similar to those of intermittent streams during periods of flow intermittency versus times of continuous flow (Gómez‐Gener et al, ; Looman, Maher, Pendall, Bass, & Santos, ; von Schiller et al, ). To fully understand the role of GBs on the carbon balance of stream corridors, it is thus important to quantify the spatio‐temporal variability in the sources and magnitude of CO 2 evasion fluxes.…”
Section: Introductionsupporting
confidence: 64%
“…The unsubmerged surface of GBs has been shown to have significantly higher CO 2 evasion fluxes, as compared with the equivalent area of its adjacent stream (Boodoo, Trauth, Schmidt, Schelker, & Battin, ). These observed CO 2 evasion flux patterns are similar to those of intermittent streams during periods of flow intermittency versus times of continuous flow (Gómez‐Gener et al, ; Looman, Maher, Pendall, Bass, & Santos, ; von Schiller et al, ). To fully understand the role of GBs on the carbon balance of stream corridors, it is thus important to quantify the spatio‐temporal variability in the sources and magnitude of CO 2 evasion fluxes.…”
Section: Introductionsupporting
confidence: 64%
“…This study showed that pCO 2 , pCH 4 , and pN 2 O increased with stream flow in the high wetland and one of the intermediate wetland, first‐order streams and either decreased or had no relationships in low wetland and forested, first‐order streams. Most previous work has shown dilution of CO 2 and CH 4 concentrations with increasing discharge (Billett & Harvey, ; Dinsmore & Billett, ; Dinsmore et al, , ; Looman et al, ; Wallin et al, ). The positive relationships in this study are probably due to sampling close to wetland sources.…”
Section: Discussionmentioning
confidence: 95%
“…When examining these mechanisms in the field, studies find both positive and negative relationships between pCO 2 and discharge. Most studies of this nature have occurred in headwater, peatland systems, and report negative relationships between instantaneous discharge and CO 2 (Billett & Harvey, 2013;Dinsmore et al, 2013Dinsmore et al, , 2010Dinsmore & Billett, 2008;Looman et al, 2017;Wallin et al, 2010) and CH 4 (Dinsmore et al, 2013(Dinsmore et al, , 2010Hope et al, 2001). However, a headwater stream in permafrost-influenced interior Alaska showed a positive relationship between pCO 2 and discharge during storms at a downstream site and a negative relationship at an upstream site (Crawford et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mediterranean areas or Australia (e.g. Gomez-Gener et al 2015;Looman et al 2017). Here we show that such stream intermittency can also cause high and rapid CO2 pulses in a Swedish agricultural setting, highlighting the need for expanding the geographical coverage of studies that investigate stream intermittency in relation to GHG dynamics and emissions.…”
Section: Discussionmentioning
confidence: 99%